Experimental Study on Novel Energy-Dissipating Prefabricated Beam-Column Joints - Qiong Liu; Shanghong Chen; Wei Lin; Fanjin Zeng (Advances in Civil Engineering)
A new dapped-end beam to column connection is designed in this paper. Its assembly connection zone changes from inside the joint to midspan of the beam. The proposed connection can not only provide good structural integrity but also ensure that the plastic hinge moves away from the column edge. The rotational capacity of the plastic hinge determines the internal force redistribution of the joint and the energy dissipation capacity. The high-strength bolts and steel plates are used to realize connection, further enhancing the rotation of the plastic hinge and minimizing the cast-in-place concrete volume. Three full-scale exterior beam to column joints are casted and then subjected to reversal cyclic loading. The finite element (FE) analyses are carried out to compare with experimental results and study the effect of connection position on the structural behaviours. The obtained results show that the plastic hinges of all three specimens are firstly developed to a distance from the column edge, thus revealing that this kind of joint can achieve beam hinge mechanism and prevent joint shear failure. And the connection position is the most disadvantaged when coinciding with the plastic hinge zone, which would result in the excessive deformation and the early failure of the steel bar anchor system. The new type of joint shows good seismic performance during earthquake if the connection can be properly designed, and thus this kind of structural form can be applied to actual engineering structures in seismic regions.